Morphological study of Cyclotella distinguenda with a description of a new fossil species Cyclotella paradistinguenda sp. nov. from the Agios Floros fen, SW Peloponnese, Greece in relation to other Cyclotella species. Issue 3 (2nd July 2016) - Katrantsiotis, Christos; Risberg, Jan; Norström, Elin; Holmgren, Karin
Abstract : In a previous palaeoenvironmental study based on a high-resolution diatom record from a core sampled at the Agios Floros fen, SW Peloponnese, Greece, Cyclotella distinguenda was reported as exhibiting two morphs with distinct central area and stria arrangement, as well as a specific distribution throughout the sequence. In the present paper, we examine this morphological variability through detailed observations using light and scanning electron microscope combined with a simple statistical approach. Our new data suggest that the two morphs present substantial and constant differences in the structure and size of their central areas, the structure and number of their striae, the arrangement of their marginal fultoportulae/density of costae between fultoportulae, the shape of their rimoportulae and their alveolar chambers. On the basis of these morphological and stratigraphic variations one morph is described as a new species, Cyclotella paradistinguenda sp. nov., while the other is assigned to C. distinguenda and is also consistent with the original description of this taxon. The two species share well-defined central areas without fultoportulae, almost equal length striae and one rimoportula situated on a costa within the ring of marginal fultoportulae. Cyclotella paradistinguenda sp. nov. can be distinguished by a combination of the following characteristics: (1) large central area (≤1/3 of valve diameter), smooth or decorated with puncta and depressions, flat or concentrically undulated, (2) distinct, narrow striae (12–15/10 µm) consisting of one or two short rows of areolae of the same size expanding into three rows at the mantle, (3) marginal fultoportulae on each first to third costae (4) poorly developed alveolar chambers and rimoportula. Based on the stratigraphic distribution and the associated flora in the Agios Floros sequence, it can be inferred that C. paradistinguenda sp. nov. is tolerant of shallower water conditions with lower nutrient availability and/or higher pH than C. distinguenda .